The Development of Training Management Model of Soft Skill Learning Integrated With Chemo-Entrepreneurship (CEP) For High School Chemistry Teachers in Semarang - Utomo, Anang Budi; Widodo, Joko; Supartono, Supartono; Haryono, Haryono (Universitas Negeri Semarang, 2016)
Training management of learning for high school chemistry teachers in Semarang has not been implemented properly. It can be seen from the need analysis of chemistry teachers that have not been managed well. Pedagogical competence of teachers is not optimal, so that it is necessary for developing a better training management model. This study aims to analyze the factual model, design the hypothetical model, and set the final model of training management for high school chemistry teachers in Semarang, along with the effectiveness test. The research method used was research and development method. The results showed that in the factual model, the need analysis of training was not done, so the relevance was low and the learning process was less attractive and meaningful. Moreover, the control was also not carried out effectively so it could not assess the reaction and the impact of the training. Based on that factual model, the researcher arranged hypothetical model and then compiled the final model that is the development of training management model of Chemo-entrepreneurship (CEP) integrated soft skill learning for high school chemistry teachers in Semarang. The training management model includes three stages: (1) the planning stage; (2)the implementation stage; and (3)the control stage. The Training Management Model of Soft Chemo-Entrepreneurship Integrated Soft Skill Learning (MPPSS-CEP model) has high level of effectiveness and it is easy to be implemented for high school chemistry teachers.